Unexplored Potential in Online In-service Teacher Professional Development towards teaching with technology: Teacher Perceptions, Challenges and Spill-Over Effects in Kenya - K. Kiarie, Bernadette; Wairua, Ian; Wairua, Monica (RA Journal of Applied Research, 2021)
Online courses can provide a worthwhile alternative to on-site Teacher Professional Development (TPD) especially in developing countries such as Kenya. This study was based on a training intervention which helped teachers to cope with the sudden turn of events that came after the government closed schools as one of the COVID-19 containment measures. A private university in Kenya designed and launched an online in-service course to respond to the needs of teachers amidst the pandemic. The university’s Teacher Enhancement Programme (TEP) realized that the training proved to be a game changer for the group of teachers who participated. The online training intervention enabled the teachers to get in touch with learners who were otherwise inaccessible. This study is a descriptive survey with both quantitative and qualitative data from a post survey questionnaire and a focused group discussion. The outcomes of the study indicated that online teacher enhancement programmes are an uncharted potential option for TPD even though there were challenges. The training intervention boosted teacher confidence in using technology to teach, and encouraged them to venture and discover more technology-based teaching tools on their own. The training intervention also led to improved teacher performance in the employment of emergency remote teaching within their learning institutions.